SHOCK-WAVE THERAPY OF ENTHESOPATHYS - Чорний, Вадим; Чорний, Владислав (SWorldJournal, 2023)
Repeated stereotypic or periodic explosive loadings are able to cause painful conditions both with people professionally connected with such loadings and undertrained and elderly people who make the overwhelming majority of city dwellers. In publication